Unionization, information asymmetry and the de-location of firms - Marco De Pinto; Jörg Lingens (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2014)
We analyze the effects of unionization on the decision of a firm to either produce at home or abroad. We consider a model in which home and foreign workers are perfect substitutes and firms have an informational advantage concerning their productivity. The union offers wage-employment contracts to induce truthtelling. Because of a firm's productivity dependent outside option (producing abroad), the problem is characterized by countervailing incentives. We find that, under fairly mild assumptions on the distribution of firm's productivity, the overstating incentive always dominates. The equilibrium contract offered by the union is then characterized by overemployment. Besides its effect on the intensive margin, the union also affects the extensive margin (i.e. de-location). The union forces firms to de-locate because this narrows the possibility to overstate productivity which then saves rent payments to the firm.
Keywords: J51; F2; D82; 330; trade unions; information asymmetry; open economy; countervailing incentives; de-location